The Australian Acoustic Observatory. Issue 10 (10th July 2021) - Roe, Paul; Eichinski, Philip; Fuller, Richard A.; McDonald, Paul G.; Schwarzkopf, Lin; Towsey, Michael; Truskinger, Anthony; Tucker, David; Watson, David M.
Abstract: Fauna surveys are traditionally manual, and hence limited in scale, expensive and labour‐intensive. Low‐cost hardware and storage mean that acoustic recording now has the potential to efficiently build scale in terrestrial fauna surveys, both spatially and temporally. With this aim, we have constructed the Australian Acoustic Observatory. It provides a direct and permanent record of terrestrial soundscapes through continuous recording across Australian ecoregions, including those periodically subject to fire and flood, when manual surveys are dangerous or impossible. The observatory comprises 360 permanent listening stations deployed across Australia. Groups of four sensors are deployed at each of 90 sites, placed strategically across ecoregions, to provide representative datasets of soundscapes. Each station continuously records sound, resulting in year‐round data collection. All data are made freely available under an open access licence. The Australian Acoustic Observatory is the world's first terrestrial acoustic observatory of this size. It provides continental‐scale environmental monitoring of unparalleled spatial extent, temporal resolution and archival stability. It enables new approaches to understanding ecosystems, long‐term environmental change, data visualization and acoustic science that will only increase in scientific value over time, particularly as others replicate the design in other parts of the world.